Knowledge about Cervical Cancer among Women of Reproductive Age Attending a Tertiary Level Hospital in Bangladesh - Begum, Nasima; Sumaya, Maliha; Jahan, Hasna; Akter, Shilpy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Cervical cancer is the fourth mostfrequent malignancy in women worldwide. The highest rate of this cancer incidence and mortality are in low- and middle-income countries. It is thesecond leading cause of cancer-related deaths among women in Bangladesh. To assess the level of knowledge among women of reproductive age about cervical cancer. Materials and methods: This descriptive cross-sectional study was conducted from September 2019 to December 2019 in the Gynecology and Obstetrics Outpatient Department (OPD) of Sir Salimullah Medical College and Mitford Hospital. The sampling technique was purposive. A total of 300 women of reproductive age (15 to 49 years) were interviewed using a pretested semi-structured questionnaire. Results: Most participants (75%) did not know aboutcervical cancer. Only 34.7% of women reported understanding symptoms and one-fourth (25%) knew the causes of cervical cancer. Conclusion: Knowledge about cervical cancer among women was revealed to be remarkably poor. Health education and community-based intervention should focus on informing risk factors, symptoms, screening and cervical cancer vaccination. In the future, this study will assist with planning various strategies including sexual health, participation in screening and preventive services. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 17-21